Images without words—the focus group as a method of examining the reading experience of comics - Pitkäsalo, Eliisa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
This article presents a pilot study conducted in Hungary and Italy in the autumn of 2015. The study had two goals: to test the method of focus-group discussion for collecting data on a multimodal reading experience and to collect information on participants’ reading experience with comics, with an emphasis on their ability to understand the visual language of comics. The study examined the importance of the verbal mode in understanding non-verbal messages and the way in which the role cultural background and the competence to read comics affect participants’ interpretations of the meanings of the visual content of comics. In addition to answering the main research questions, the article reflects on focus groups as a data-collection method. The study indicated that cultural background, including the tradition of reading comics, may have an effect on enhancing participants’ understanding of the visual content of comics, which is also an important aspect the translator has to take into consideration.